A Case Study of User-Centred Design in Four Swiss RUP Projects - Ljiljana Vukelja; Klaus Opwis; Lothar Müller (Advances in Human-Computer Interaction)
We analysed four Rational Unified Process (RUP) projects in Switzerland that identified themselves as following a user-centred approach. Grounded theory served for analysis of 12 interviews with software developers, project managers, and UI specialists. For each professional group we analysed their work context, motivations, work practices, and strategies used to overcome the obstacles to user-centred design. Results show that end users did not participate in the projects. Instead of working directly with end users, participants used data from marketing research or consulted colleagues from other departments. Prototypes played an important role. We suggest the following remedies: (1) developing methods for easy integration of existing company knowledge about products with usability features, (2) professionalising UI design by educating project stakeholders in standard UI design, (3) creating an approved pool of company's personas for UI specialists' work, and (4) educating customers on their right to get good user interfaces.